2007
DOI: 10.1080/17453670710014185
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged thromboprophylaxis with Dalteparin during immobilization after ankle fracture surgery: A randomized placebo-controlled, double-blind study

Abstract: BackgroundSkeletal trauma and immobilization are well-known risk factors for deep vein thrombosis (DVT) and pulmonary embolism (PE). While prophylaxis against thromboembolic complications has become routine after major orthopedic surgery, whether or not prophylaxis after minor surgery and lower limb immobilization is necessary is still under debate.Methods In a double-blind, placebo-controlled study, 272 consecutive patients were randomized to receive either thromboprophylaxis with Dalteparin (n = 136) or plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
117
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 17 publications
5
117
1
3
Order By: Relevance
“…The frequency of DVT in the control group (37%) found in this study is in agreement with previously reported, 36%, in other randomized controlled studies on CDU verified DVT after surgical treatment of acute ATR (6)(7)(8). The characteristics of the patient population in this study did not differ from that of the three earlier studies reporting on DVT rates after ATR surgery (7,8,16).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The frequency of DVT in the control group (37%) found in this study is in agreement with previously reported, 36%, in other randomized controlled studies on CDU verified DVT after surgical treatment of acute ATR (6)(7)(8). The characteristics of the patient population in this study did not differ from that of the three earlier studies reporting on DVT rates after ATR surgery (7,8,16).…”
Section: Discussionsupporting
confidence: 82%
“…Earlier investigations demonstrated no DVTpreventive effect with LMWH in ATR patients. (6) This study, however, established IPC prophylaxis as a feasible and efficient treatment alternative, at least during early immobilisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] Lapidus et al, [36] however, found a 28% DVT rate in patients after ankle fracture surgery who did not receive pharmacological prophylaxis. In two studies following Achilles tendon rupture repair, the incidences of DVT were 36% [19] and 6%.…”
Section: Researchmentioning
confidence: 99%
“…[12][13][14] Studies assessing the safety of long-term LMWH against oral vitamin K antagonists (VKAs) or novel anticoagulants in cancer or other populations were designed to address more common side effects: the risk of bleeding and thrombocytopenia. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] The adverse effects of long-term LMWH on bone in terms of increased risks of fractures (i.e., clinically most important but rare outcomes) and bone loss are less commonly researched and unclear. The effects of LMWH on bone were mainly studied in the pregnant population.…”
Section: Introductionmentioning
confidence: 99%